2019
DOI: 10.1208/s12249-019-1412-1
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of Carbamazepine in TPGS Micelles: Effect of Temperature and Electrolyte Addition

Abstract: D-α-Tocopheryl polyethylene glycol succinate (TPGS), a polyethylene glycol condensate, is a biologically important nonionic amphiphile. In this study, we report on aqueous solution behavior of TPGS with a focus on its clouding, surface activity, micellar characteristics, and solubilization capacity for a model hydrophobic drug, carbamazepine (CBZ). Micelles were characterized by dynamic light and small-angle neutron scattering studies as a function of temperature, salt addition, and CBZ solubilization. TPGS sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Therefore, the micellar size values obtained for TPGS (~14 nm) and PF127 (~40 nm) fit the size range expected for the renal accumulation of these nanocarriers. Regarding TPGS micelles, our results support previous studies that have reported no marked changes in Dh with increases in temperature of up to 40 °C [ 25 ]. On the contrary, the micellization of PF127 was affected by changes in temperature.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the micellar size values obtained for TPGS (~14 nm) and PF127 (~40 nm) fit the size range expected for the renal accumulation of these nanocarriers. Regarding TPGS micelles, our results support previous studies that have reported no marked changes in Dh with increases in temperature of up to 40 °C [ 25 ]. On the contrary, the micellization of PF127 was affected by changes in temperature.…”
Section: Discussionsupporting
confidence: 91%
“…Here, high loading emanated from the synergism between micellar encapsulation and binding interaction between the drug and the non-polar region [ 31 ]. It is argued that hydrophobic interactions are augmented during drug encapsulation, and it sometimes triggers contraction of the core, as reported earlier by our group in the TPGS-carbamazepine system [ 13 ]. These differences can be related to the molecular size of payloads: small hydrophobic molecules impose less steric constraints and, hence, offer better engagement with the core block.…”
Section: Resultsmentioning
confidence: 52%
“…With a low critical micelle concentration (CMC, 0.02% w / w ) and a micelle aggregation number close to 100, TPGS has been used as a safe adjuvant in the development of various colloidal formulations. Earlier studies, including ours, have demonstrated that it forms core-shell micelles which remain stable with temperature and concentration [ 12 , 13 , 14 , 15 ]. Apart from biosafety, TPGS possesses interesting biological properties relevant to drug delivery in cancer cells [ 16 ].…”
Section: Introductionmentioning
confidence: 80%
“…This trend is evident also for the loaded micelles, where the formulation with the highest drug loading is characterized by the smallest sizes. It is argued that hydrophobic interactions are augmented during drug encapsulation, and this sometimes triggers contraction of the core, as previously reported in the TPGS-carbamazepine system [ 39 ]. Concerning the Zeta potential, since TPGS does not possess ionizable groups, its surface charge is almost neutral ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 67%